BIMSTEC: the journey and the way ahead - Datta, Sreeradha (New Delhi : Pentagon Press, 2021)
"While the lack of perceived progress within Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation (BIMSTEC) has led to scepticism about its goal and ability to deliver, cooperation within BIMSTEC assumes paramount importance given the present state of international cross-border permeability."--
Keywords: Regionalism; India -- Bay of Bengal; International economic relations